Traditional Products and New Developments in the Restaurant Sector in East Africa. The Case Study of Nakuru County, Kenya - Zocchi, Dauro M.; Fontefrancesco, Michele F. (Frontiers in Sustainable Food Systems, 2020)
Over the last twenty years, we have witnessed worldwide a renewed interest in local food products and traditional cuisine. Addressing this demand, the catering industry has played a pivotal role in reviving local food heritage and traditions. While several studies have explored the evolution of this trend in Europe, little attention has been given to this phenomenon in contemporary Africa. To partially fill this gap in the literature, we conducted an ethnographic study to investigate the role of the catering sector in recovering and promoting food and gastronomic heritage in Nakuru County, an emerging Kenyan agricultural and tourist hub. Specifically, we aimed at understanding the main drivers behind the offering and demand for traditional ingredients and recipes. Fieldwork was conducted through the analysis of 41 restaurants and hotels, and data collection was completed through semi-structured interviews with 51 professionals, including owners, food and beverage managers, and chefs. We reported 33 recipes and ingredients tied to Kenyan culinary traditions. Some differences in the role of Kenyan cuisine emerged, with the differentiation mostly linked to the customer profiles. In particular, attention towards traditional foods was more accentuated in restaurants aimed at middle- and high-income Kenyan customers and for specific products namely African leafy vegetables and indigenous chicken, locally known as kuku kienyeji. Concurrently, we discovered that the inclusion of these products on the restaurant menus implied an incipient localization of the food supply chains based on self-production or direct commercial relationships with small-scale producers. The research highlighted how the relaunch of traditional food and cuisine develops from a demand for healthy and natural products rather than a search for cultural authenticity. Based on the specificities of the local market, this fosters the creation of alternative supply strategies to cope with the poor quality of ingredients, price fluctuations, and discontinuity of the supply. In this sense, the research suggests also considering tangible factors linked to the technological and logistical conditions of the trade and safety of food to understand the drivers behind the rediscovery of local and traditional foods.